Addressing the political dynamics of radicalization leading to religious extremism in Bangladesh - Md. Nazmul Arefin; Nousheen Sharmila Ritu (SIMULACRA: JURNAL SOSIOLOGI, 2021)
When radicalization and religious extremism is predominantly perceived through the prism of ‘9/11’ and/or ‘Post-Soviet Muslim radicalization’, there is a danger of oversimplifying the phenomenon of extremism for majoritarian Muslim societies like Bangladesh. To understand the dynamics of religious radicalization, it is imperative to devise a political genealogy and identify both micro and macro level political drivers of radicalization by addressing the political histories, catalysts, and risk factors related to religious extremism. Considering the paucity of research on this particular area, this paper sets out to understand and address the political drivers that facilitate the process of radicalization leading to religious extremism in Bangladesh. Adopting qualitative approach, this paper has conducted content analysis of pertinent secondary sources based on predetermined sets of categories for analysis. The results indicate that explicit support by the military rulers for Islamic orthodoxy, culture of political opportunism in democratic regimes and weak governance are some of the major political drivers of radicalization and religious extremism in the country. At a regional and global level, insurgency and separatist movements in neighborhood countries, global political environment of confrontation between the West and the Muslim World and the identity politics altogether fostered radicalization leading to religious extremism in Bangladesh.